"You did not desert me my brothers in arms": The continuing bond experience of men who have lost a brother in arms. Issue 2 (7th February 2022) - Mahat-Shamir, Michal; Lebowitz, Keshet; Hamama-Raz, Yaira
Abstract: This qualitative study provides an in-depth account of the continuing bond experience of bereaved Israeli men who have lost a comrade with whom they served in mandatory military service (a brother in arms). Our study findings indicate that bereaved men experienced continuing bond relationships with their deceased brothers in arms on two axes—an internal axis and an external axis. Together, the two axes connected the bereaved to the deceased. Furthermore, the bereaved constantly (re)negotiated these connecting axes vis-a-vis Israeli social norms and expectations. Implications for practice are outlined.